Understanding the 'water footprint' of beef - International Livestock Research Institute (International Livestock Research Institute, 2022)
It's commonly cited that it takes 15,000 litres of water to produce 1 kilogram of beef. This is its so-called 'water footprint'. But in order to produce beef sustainably, we need to understand where this popular figure comes from, and what types of water it refers to. Are there any scenarios where this figure would change? Of course there are - watch the video to find out more! Original source: Mekonnen, M., & Hoekstra, A. (2012). A Global Assessment of the Water Footprint of Farm Animal Products. Ecosystems, 15(3), 401-415. doi: 10.1007/s10021-011-9517-8